If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8(-2x + -5) + -4x = 88 Reorder the terms: -8(-5 + -2x) + -4x = 88 (-5 * -8 + -2x * -8) + -4x = 88 (40 + 16x) + -4x = 88 Combine like terms: 16x + -4x = 12x 40 + 12x = 88 Solving 40 + 12x = 88 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + 12x = 88 + -40 Combine like terms: 40 + -40 = 0 0 + 12x = 88 + -40 12x = 88 + -40 Combine like terms: 88 + -40 = 48 12x = 48 Divide each side by '12'. x = 4 Simplifying x = 4
| -34=-4(x+4)-5x | | y=(8-6k)x | | 3y-9x=21 | | 3a=2*12 | | 9(x+8)+6=4(x+7) | | -3x+4+3x-3=5 | | 1.09=1.3h | | 9c=7*54 | | 6x-2+7x=180 | | 5x-8+3x=24 | | (2x+7)(x+5)= | | 8=4x+4-3x | | 8(z-6)=-16 | | 2212=-14c | | 14d=126*3 | | -8(4v+5)=-104 | | 3[4y+2(x-3)+2y-4]= | | -2(y-5)= | | -4(2x-2)=22 | | 456=6x+308 | | 12x+5y+7= | | 5x-10=8x+6 | | 4ax=6 | | 23p=529 | | 1/5(5x+20)4/1-5= | | 5-(-8)-40+(-2)= | | 3x-31-x+6= | | 6x-(3x+7)=4x-10 | | 5=(-2x)+3x | | -3y=471 | | -32=3x+10 | | -106+2x=92-7x |